2015
DOI: 10.1186/s40696-015-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychological impacts from the 2011 Great East Japan Earthquake Disaster: a systematic literature review

Abstract: BackgroundOn March 11, 2011, Japan experienced an unprecedented combination of earthquake/tsunami/nuclear accidents (the Great East Japan Earthquake; GEJE). We sought to identify mental health and psychosocial consequences of this compound disaster.MethodA systematic literature review was conducted of quantitative research articles addressing mental health of survivors and the psychological impact of the GEJE. For articles between March 2011 and December 2014, PubMed, PsychINFO, and EMBASE databases were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 64 publications
2
62
0
Order By: Relevance
“…Though there has been much research on the psychological impact of disasters on individuals (Harada et al, 2015;Leon, 2004;Neria et al, 2007), there has been less attention on the effect of experiencing disasters as part of a group. Many people experience traumatic incidents as part of an occupational group -for example, an office affected by a fire or an organisation targeted by terrorists.…”
Section: Introductionmentioning
confidence: 99%
“…Though there has been much research on the psychological impact of disasters on individuals (Harada et al, 2015;Leon, 2004;Neria et al, 2007), there has been less attention on the effect of experiencing disasters as part of a group. Many people experience traumatic incidents as part of an occupational group -for example, an office affected by a fire or an organisation targeted by terrorists.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological consequences of large earthquakes on survivors have been widely studied (e.g., Bland et al 1996;Chen et al 2007;Harada et al 2015). Although the seismic tremors felt in Singapore are generally weak, the resulting psychological effects on the inhabitants should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Or, one may associate this decreased motivation with symptoms of post-disaster mental issues, such as depression and PTSD (e.g., DeSalvo et al 2007;Harada et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a tsunami that occurred in Thailand in 2004, Hiransuthikul et al (2005) reported the prevalence of severe skin and soft-tissue problems among people who survived the waves yet exposed their wounds to the water. Harada et al (2015) reviewed 49 studies on mental health issues among GEJE survivors; these studies consistently identified a large proportion of survivors as suffering from posttraumatic stress disorder (PTSD), depression, and anxiety symptoms. At the interpersonal and community level, disaster survivors often experience disruptions to their relationships due to bereavement and relocation (Lindell 2013;Norris et al 2002).…”
Section: Disaster Experiences Post-disaster Life Situations and Posmentioning
confidence: 99%